Cu K-edge XANES: polymer, organic, inorganic spectra, and experimental considerations. (27th July 2017) - Larsson, Mikael; Lindén, Johan B.; Kaur, Simarpreet; Le Cerf, Brock; Kempson, Ivan
Abstract : In pursuit of design and characterisation of Cu adsorbing in thin films, we present data from a large variety of Cu-K edge X-ray Absorption Near Edge Spectroscopy (XANES) spectra obtained from organic and inorganic standards. Additionally, we have explored the impact of beam damage inducing redox alterations. Polymer nanoparticles were tested against films to produce higher concentration samples while maintaining high surface area to bulk effects. Spectra from nanoparticles were highly comparable to thin films of ~8 nm thickness, implying comparable contributions by surface effects on copper association. Finally, we observed no impact on Cu XANES spectra from vitrification with dimethyl sulfoxide to produce amorphous frozen, hydrated samples. The spectra should act as a valuable resource in assisting the design of experiments and identification of copper associations.